Biochar partially offset the increased ammonia volatilization from salt-affected soil. Issue 9 (29th July 2021) - Liu, Shimeng; Li, Yawei; Xu, Junzeng; Ma, Wenjin; Liu, Boyi; Wang, Haiyu; Liu, Xiaoyin; Luan, Yajun
ABSTRACT: Ammonia (NH3 ) volatilization is one of the major forms of nitrogen (N) losses from soil after N fertilization, especially in salt-affected soil, which leads to low N use efficiency. To evaluate the effect of biochar on NH3 volatilization from salt-affected soil with two different N fertilizers (urea and ammonium sulfate (AS)), experiments were conducted with two salt-affected soils (electrical conductivity EC1:5 of 1.0 and 5.0 ds m −1, namely S1 and S2) and non-saline soil as control (S0, EC1:5  < 0.3 ds m −1 ). Biochar was applied to S1 and S2 at the dosage of 20 t ha −1 . Results showed that increasing soil salinity significantly promoted NH3 volatilization by 38.7%–76.8% than control and AS treatments recorded higher NH3 volatilization than urea in all salinity levels. The addition of biochar decreased NH3 volatilization by 10.8%–20.9%. The proportion of cumulative NH3 volatilization in the first week to the whole experimental period was significantly higher in S1, and biochar addition can reduce the percentages of gaseous N losses. This study unravels the immense capability of salt-affected soil to aggravate N losses in the form of NH3 volatilization, and biochar can be used as a potential soil amendment in decreasing NH3 volatilization in salt-affected soil.